Empirical Study of the Impact of Unemployment on Political Stability in Iran (1985-2015) - habib samani; robabeh khilkordi (پژوهش‌های برنامه و توسعه)
Providing jobs for the recruited workforce is one of the social and legal demands of the people of every country. So far, the political effects of unemployment and employment have been less popular. Creating employment can increase legitimacy and acceptance of governments and enhance political stability. The purpose of this paper is to investigate the effects of unemployment on political stability during the period 1985-2015 in Iran. Vector regression (VAR), Johansson-Juselius, Vector Error Correction Model (VECM), and variance analysis function were used for this purpose. The results show that in the long run, two variables of unemployment rate and Gini coefficient have a negative and significant relationship with political stability. In addition, the increase in economic growth has led to a 10% improvement in the political stability index. The vector error correction model shows that the long-term pattern of political stability in each period corrects 11.9 percent of the imbalance and approaches its long-term trend. Regarding the results of the analysis of variance, the effect of the unemployment rate on political stability variance increases from 15% in the short term to 22% in the long run. According to the results of the study, it seems that in order to establish political stability in the country, the unemployment rate should be restrained in the first place and the Gini coefficient should be reduced and the economic boom in the country should be created by strengthening domestic production and following the pattern of resistance economy.